Wounding and Phospholipase C Inhibition: Evaluation of the Alkaloid Profiling in Opium Poppy - Barbora Hans; Ema Balažová; Svetlana Dokupilová; Peter Mikuš; Andrea Balažová; Renáta Kubíková; Marek Obložinský (Plants)
Wounding triggers complex secondary metabolic pathways in plants, including benzylisoquinoline alkaloid (BIA) biosynthesis in opium poppy (Papaver somniferum L.). This study explores transcriptional and metabolic responses to wounding and methyl jasmonate (MeJA) treatment, focusing on BIA biosynthesis and regulatory mechanisms. Real-time expression analysis revealed significant up-regulation of transcripts in the (S)-reticuline and papaverine biosynthetic pathway, while the noscapine pathway was suppressed. The morphinan pathway also showed transcriptional activation, except in the case of codeinone reductase (COR), which remained unresponsive to both wounding and MeJA, suggesting a partially uncoupled mechanism. Metabolite profiling using HPLC-MS demonstrated a rapid accumulation of morphine post wounding, further supporting the hypothesis of independent regulatory control over COR. The role of phospholipase C (PLC) in modulating wound-induced BIA accumulation was investigated, revealing that PLC inhibition reduced morphine production and suppressed COR expression. These findings highlight the importance of phospholipid-dependent signalling in activating morphine biosynthesis, potentially at the expense of other BIAs. This study provides insights into plant stress responses and suggests strategies for enhancing BIA production through targeted interventions, offering potential applications in improving alkaloid yield.